Rediscovering the Hiwar Method: Revitalizing An-Nahlawi’s Dialogue Approach in Contemporary Islamic Education - Aswan Aswan; Abd. Mukti; Asnil Aida Ritonga (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study examines the contemporary relevance of the Hiwar method, developed by Imam Abdurrahman An-Nahlawi, within the context of Islamic education. Rooted in classical Islamic traditions, the method prioritizes dialogue as a central teaching approach, aligning with Qur’anic and Prophetic principles of wisdom and effective communication. It offers a pedagogical alternative to Western-oriented approaches, emphasizing critical thinking, deep understanding, and character development. Using a mixed-methods framework, this study incorporates qualitative analysis of Islamic educational principles alongside empirical classroom evaluations. The research explores the applicability of the Hiwar method in addressing the challenges posed by globalization and the digital age. The study finds that the Hiwar method enhances active participation and critical inquiry, fosters meaningful and engaging learning experiences, improves communication skills, and promotes empathy, tolerance, and cooperation among students. These outcomes suggest that the method is dynamic and effective for addressing declining student motivation and the superficial grasp of religious values in contemporary education. The findings highlight the potential of the Hiwar method to revitalize classical Islamic educational practices while addressing the needs of today’s learners. Its integration into modern curricula offers a strategic means of bridging educational gaps created by rapid technological and cultural shifts. The Hiwar method serves as a valuable pedagogical strategy, combining tradition with innovation to address contemporary educational challenges. Further research should explore its broader applications and effectiveness across diverse educational settings.